War in international society - Pejcinovic, Lacy (Milton Park, Abingdon, Oxon : Routledge, 2013)
'Is war an institution of international society and how is it constituted as such across the evolution of international society? This book is an inquiry into the purpose of war as a social institution, as originally put forward by Hedley Bull. It offers a comprehensive examination of what is entailed in thinking of war as a social institution and as a mechanism for order'--
1. The theory of international society and institutions -- 2. Infidels, barbarians, and Dominium -- 3. Kings and heretics in late medieval war -- 4. Great powers and war in the nineteenth century -- 5. Historical time, commerce, and tutelage -- 6. Wars of decolonisation -- 7. The era of total war.
Includes bibliographical references : pages [207]-227) and index.
Mode of access : World Wide Web.
Keywords: War and society -- History